Temperature rise in a tropical south-eastern Asian city, Johor Bahru, Malaysia, caused by extended urbanization: numerical analysis for 1970, 2000, and 2020 based on land-use distribution - Kitada, Toshihiro; Kobayashi, Eisuke Kobayashi; Kurata, Gakuji; Ho, Chin Siong (2006)
Annual average of observed temperature at Senai (International Airport of Johor Bahru, JB) in the suburbs of JB,Malaysia has been increased by about 1.1°C for the last three decades. In the present study, this phenomenon as investigated numerically by using PSU/NCAR meso-scale model (MM5) with land-use of 1970 and 2000 so that possible contribution of extended urbanization of JB to the temperature rise was evaluated. Additionally, possible temperature increase in 2020 was also calculated based on a city planning of JB. Obtained results showed: (1) estimated increase of daily-and-area-averaged temperature was 0.64°C in the suburbs and 0.87°C in the city center of JB for the thirty years from 1970 to 2000; (2) further increase of 0.89°C was predicted in the city center from 2000 to 2020 with a town planning of Johor Bahru; (3) that urbanization in Singapore may significantly affect the temperature in JB was also suggested.